Assessing animal health delivery for tick and tick-borne disease control in smallholder dairy systems of Kenya: an application of new institutional economics. - Ndung'u, L.W. (University of Pretoria, 2002)
This thesis describes a two-component study undertaken in smallholder dairy systems of Central Kenya. One component characterized delivery systems for tick and tick-borne disease (TTBD) technologies including treatment packages, tick control products and vaccines, while the second component evaluated the important factors in their utilization by farmers. A combination of two economic analytical tools was used for the characterisation component. The first, the structure-conduct-performance (SCP) framework, was used to evaluate the performance of marketing systems and compare it to a perfectly competitive model, and the second, the new institutional economics (NIE) framework, was used to analyse the role of transaction costs in the delivery of products and services and their access by farmers. A probit model was applied to identify the specific factors that farmers consider in their choices of animal health services. Recommendations were made for the optimal pathways to deliver East Coast fever vaccines to smallholder farmers. The study was conducted in three phases. The first phase involved a cross- sectional survey of 344 smallholder dairy farmers in the central highlands of Kenya, using a structured questionnaire. These farms were selected on a gradient of market access, with high, medium and low market access represented by Kiambu, Nakuru and Nyandarua districts, respectively. The second phase involved an exhaustive survey of all service providers delivering animal health services in the study areas. The third phase involved working backwards through the marketing chain to the distributors and suppliers of technologies, as well as interviewing key informants at policy and institutional levels. Delivery of TTBD products and services was found to be highly competitive, mostly carried out by paravets (35% of the total) and stores (33%), particularly in rural areas. Vets (18%) had a higher distribution in peri-urban areas, and their limited distribution in rural areas raised the transaction costs associated with rural farmers’ search and screening for high quality services. There were no formal regulatory bodies supervising the quality of the products and services being supplied to farmers and no state restrictions existed on the type of service providers selling tick control products. Although pyrethrines (pour-ons) were only permitted for tsetse control, they were freely being sold to farmers for tick control. A live vaccine, the infection and treatment method (ITM) for ECF immunization, was available in the country but its sale was restricted to a single site, the Kenya Coast. Thus, this vaccine was not available in the study areas. The study identified three key problems that require specific policy intervention: i) poor access of services and products by farmers, with an undefined role of paravets who are presently under-utilized, ii) information asymmetries among farmers and the need to enforce service quality control of products and services, iii) lack of voice among smallholder farmers with no leverage for compensations in cases where they receive poor or inappropriate services. Several transaction costs were identified as constraining the utilization of animal health services by farmers, and ranged from information, through negotiation to monitoring costs. Farmers considered the ethnicity and the service quality (as determined by past performance) of the nearest service provider as important in their choices, and the density of service providers over a given radius around each farm as well as travel time to a service provider were crucial determinants in farmer decision-making. Using a combination of economic and epidemiological approaches, the study assessed supply and demand issues associated with delivery pathways for ECF vaccines among smallholder farmers. The supply-side component involved evaluating transaction costs associated with two ECF vaccines; ITM and a sub-unit vaccine under development, and identifying the appropriate role of public and private sector in delivery. The main constraints associated with ECF vaccine delivery and requiring appropriate policies included high information asymmetries faced by farmers, lack of appropriate quality control and limited accessibility to products and services by farmers. On the demand side, ECF risk was found to vary with cattle production systems and agro-ecology. Potential demand for vaccines was found to be high in both Nyandarua and Nakuru districts and relatively low in Kiambu, where zero-grazing reduces risk substantially. The study recommends utilization of paravets for ECF vaccine delivery as an effective means of reducing transaction costs by increasing service penetration especially in rural areas where the density of veterinarians tends to be low.